Sense of belonging in an ecuadorian’s university students in pandemic times - Roque-Herrera, Yosbanys (2022)
The sense of belonging implies the creation of bonds of commitment of the individual with his social group or organization to which he belongs. The purpose of the research process was to establish the status of the dimensions inherent to the sense of belonging in students of the Graphic Design career at the National University of Chimborazo during the academic period November 2020 - April 2021; through an observational, descriptive, and cross-sectional cost study, whose study population was made up of 66 students from this educational context, who decided to participate voluntarily. The determining factors questionnaire was applied to assess the sense of belonging in university students. 98.48% of the participants were under 30 years of age and 66.66% belonged to the male gender. The values of the means in the measured factors ranged between 2.27 and 3.25, predominant category quite. The social dimension was the worst rated by those involved. Factors related to professional training, pride in their institution and the way in which it prepared its virtual teaching scenarios were the best perceived by the participants.